IMPLEMENTATION OF MULTICULTURAL EDUCATION PROCESS IN ISLAMIC INSTITUTE OF FATTAHUL MULUK PAPUA - Rokhmah, Sitti; Juhannis, Hamdan; Yaumi, Muh.; Halim, Wahyuddin (Program Pascasarjana, UIN Alauddin Makassar, 2020)
This paper examines in depth the implementation of the multicultural education process at IAIN Fattahul Muluk Papua at conceptual and institutional levels. This type of research is qualitative research, the approach used in this research is a multidisciplinary approach with pedagogical, psychological, and sociological approaches. Data sources consist of primary data and secondary data. Data collection techniques through observation, interviews, documentation, literature search and Focus Group Discussion (FGD). The research instrument, namely, the researcher as a key instrument by using the observation theme guide, interview and documentation reference. Processing and data analysis with a model that is condensation Miles and Huberman, data presentation, conclusion and verification. Testing the validity of the data, namely triangulation techniques, checking the correctness of the information, discussing and consulting data, and extending research time. Based on the explanation above, it can be concluded that the implementation of the cultivation of multicultural education values at IAIN Fattahul Muluk Papua through the first conceptual level is realized through planning and formulating the vision, mission, and objectives of IAIN Fattahul Muluk Papua, the second institutional level is implemented through content integration. education in the curriculum) and the internalization of values in learning carried out by stages (a) transforming multicultural values; (b) multicultural value transaction and (c) the application of transinternalization of multicultural values. The three operational levels include curriculum design that is designed based on multicultural values that are applied through the formal curriculum and hidden curriculum (not included in the curriculum) which is unwritten, not programmatically planned but its existence is influential in the application of multicultural education. The four architectural levels are realized through the formation of an adequate and complete multicultural-based physical environment.